Tinjauan Kriminologi Terhadap Residivis Kasus Pencurian di Kota Kupang - Salhenover Laibahas; Rudepel Petrus Leo; Rosalind Angel Fanggi (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to analyze the criminological review of recidivist theft cases in Kupang City. This research is a type of empirical juridical research and the data collection uses interview techniques with respondents and literature studies. The data was analyzed descriptively qualitatively. The results of this study indicate that the factors causing theft crimes by recidivists are economic factors, environmental factors, family factors, opportunity factors, psychological factors. The modus operandi carried out by recidivists is to survey or monitor the location of the theft randomly and then lurk, follow, and some even block the targets in place to carry out the theft. Countermeasures against recidivists, namely preemptive efforts are prevention efforts carried out early on, and preventive efforts emphasize prevention efforts to eliminate opportunities to commit crimes that must be carried out individually, society, government and police officials. As well as countermeasures by means of coaching carried out by prisons and detention centers against recidivists are personality coaching and independence coaching. The author's suggestion is the need for support and active role from all levels of society to fully support the implementation of countermeasures carried out by the police and correctional institutions. The importance of legal awareness in oneself of the legal values that apply in a community group. Especially for correctional institutions, changes are needed in the coaching system where coaching for recidivist prisoners needs to be stricter and psychologist assistance is needed so that the mental health conditions of prisoners are checked and it is also necessary to eliminate some of the rights of prisoners such as leave before release and conditional release.